Angiotensin-II-evoked Ca2+ entry in murine cardiac fibroblasts does not depend on TRPC channels - Camacho Londoño, Juan Eduardo; Kraft, Axel E.; Schürger, Alexander; Richter, Christin; Freichel, Marc (Cells, 2020)
TRPC proteins form cation conducting channels regulated by different stimuli and are regulators of the cellular calcium homeostasis. TRPC are expressed in cardiac cells including cardiac fibroblasts (CFs) and have been implicated in the development of pathological cardiac remodeling including fibrosis. Using Ca2+ imaging and several compound TRPC knockout mouse lines we analyzed the involvement of TRPC proteins for the angiotensin II (AngII)-induced changes in Ca2+ homeostasis in CFs isolated from adult mice. Using qPCR we detected transcripts of all Trpc genes in CFs; Trpc1, Trpc3 and Trpc4 being the most abundant ones. We show that the AngII-induced Ca2+ entry but also Ca2+ release from intracellular stores are critically dependent on the density of CFs in culture and are inversely correlated with the expression of the myofibroblast marker α-smooth muscle actin. Our Ca2+ measurements depict that the AngII- and thrombin-induced Ca2+ transients, and the AngII-induced Ca2+ entry and Ca2+ release are not affected in CFs isolated from mice lacking all seven TRPC proteins (TRPC-hepta KO) compared to control cells. However, pre-incubation with GSK7975A (10 µM), which sufficiently inhibits CRAC channels in other cells, abolished AngII-induced Ca2+ entry. Consequently, we conclude the dispensability of the TRPC channels for the acute neurohumoral Ca2+ signaling evoked by AngII in isolated CFs and suggest the contribution of members of the Orai channel family as molecular constituents responsible for this pathophysiologically important Ca2+ entry pathway.
Im Titel ist "2+" hochgestellt
Gesehen am 29.04.2020